Bordersea: Jejaring, Kultur, dan Relasi Agama - Muhammad Nur Ichsan Azis; Uswatun Hasanah; Agus Mahfudin Setiawan (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2023)
Border issues have recently experienced ups and downs in academia and research after the election and reshuffle of new ministers in the Indonesian government. After Mrs. Susi Pudjiastuti, former Minister of Marine Affairs and Fisheries, was reshuffled, attention to border areas, especially maritime boundaries, between countries experienced ups and downs again. The government seems to be less focused on border discourse, which raises various problems in it. However, if we look back, border studies, especially maritime borders, will be the main attraction in maintaining state sovereignty, and the culture and identity of a nation and state. This study attempts to describe and analyze the border sea area in the world of maritime, culture, religion, entity and identity of a country and nation. The historical method is used in this study with a socio-economic approach that intersects with the processes and axis of networks, culture, and identity. The network is interpreted as a process that intersects with society, as a subject and object, which becomes one axis in human activity. In the process, a communal culture and network is formed as a characteristic of a community group as a form of personal or communal and institutional expression. The results of this study indicate that a historical process has implications for the emergence of cultural groups and ethnic identities in society. The Sulawesi Sea acts as a connecting area between countries, nations, in the scope of history and culture, so this study is expected to contribute to the study of the border area of two countries and nations.